Ten apples up on top! - LeSieg, Theo., 1904-; McKie, Roy. ([New York] Beginner Books, 1961)
A lion, a dog, and a tiger balance apples on their heads.
Keywords: Counting; Animals -- Fiction; Stories in rhyme